AKTUALISASI SAD KERTI DALAM KUMPULAN PUISI OMBAK RARÉ BALI KARYA I PUTU GEDE RAKA PRAMA PUTRA - Ni Kadek Dwi Artini; Ni Nyoman Perni; I Made Dian Saputra (Dharma Sastra: Jurnal Penelitian Bahasa dan Sastra Daerah, 2023)
The poem Ombak Raré Bali by I Putu Gede Raka Prama Putra is very much about the social themes of people's lives today and really reflects the local color of Bali. In this regard, the problem discussed in this study is How is Sad Kerti actualized in the poems contained in the collection of Ombak Raré Bali poems by I Putu Gede Raka Prama Putra? The theory used in this research is structural theory and semiotic theory. This study uses a qualitative research method, namely the method of literature and data analysis method used is descriptive analysis method. The actualization of Sad Kerti contained in the Ombak Raré Bali poetry collection, namely: 1) Atma Kerti is a life effort to always seek so that the enlightenment that is always emitted by God from all directions can connect or meet with the radiance of the purity of Atman which also always emanates from within Bhuana Alit or from within man. The titles of the poems included in Atma Kerti are: Ngiring Rumasayang, Élingang Pamargi, Puput... 2) Samudra Kerti is protecting the ocean or sea. The titles of the poems included in Samudra Kerti are: Yéh… Yéh…, Cerita Mémé 3) Wana Kerti, namely preserving forests and mountains. The titles of poems included in Wana Kerti are: Méru. 4) Danu Kerti, namely an effort to preserve fresh water sources on land such as springs, lakes, rivers and other springs. The title of the poem included in Danu Kerti is: Yéh… Yéh… 5) Jagat Kerti is an effort to build four togethernesses that are harmonious, safe, peaceful, and foster physical and spiritual well-being by implementing spiritual power that arises from worship of God. The titles of the poems included in Jagat Kerti are: Yadnya, Banten, Ngastiti Bali Santi. 6) Jana Kerti is an effort to build harmony and tolerance towards fellow human beings. The titles of the poems included in Jana Kerti are: Sami Siki, Yowana Baliné Mangkin, Titiang Raré Bali.